Respiratory Watch: Development of a Provincial System for Respiratory Syncytial Virus Surveillance in Nova Scotia, 2005–2008 - Assaad Al-Assam; Joanne M Langley; Shelly Sarwal (Canadian Journal of Infectious Diseases and Medical Microbiology)
OBJECTIVE: Respiratory syncytial virus (RSV) is the most common cause of severe lower respiratory tract infection in young children and is increasingly recognized as a cause of influenza-like illness in those older than 65 years of age. A surveillance system to provide timely local information about RSV activity in Nova Scotia (NS) is described.